Toward a Cognitive Neural Prosthesis Using Focused Ultrasound - Downs, Matthew E.; Teichert, Tobias; Buch, Amanda; Karakatsani, Maria E.; Sierra, Carlos; Chen, Shangshang; Konofagou, Elisa E.; Ferrera, Vincent P. (Frontiers in Neuroscience, 2017)
Noninvasive brain stimulation using focused ultrasound has many potential applications as a research and clinical tool, including its incorporation as either an extracorporeal or implantable neural prosthetic. To this end, we investigated the effect of focused ultrasound (FUS) combined with systemically administered microbubbles on visual-motor decision-making behavior in monkeys. We applied FUS to the putamen in one hemisphere to open the blood-brain barrier, and then tested behavioral performance 3-4 hours later. On days when the monkeys were treated with FUS, their decisions were faster and more accurate than days without sonication. The performance improvement suggested both a shift in the decision criterion and an enhancement of the use of sensory evidence in the decision process. FUS also interacted with the effect of a low dose of haloperidol. The findings indicate that a two-minute application of FUS can have a sustained impact on performance of complex cognitive tasks, and may increase the efficacy of psychoactive medications. The results lend further support to the idea that the dorsal striatum plays an integral role in evidence- and reward-based decision-making, and provide motivation for incorporating focused ultrasound into cognitive neural prosthetic devices.